2016
DOI: 10.1016/j.annepidem.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Disease-related mortality among 21,609 Norwegian male military peacekeepers deployed to Lebanon between 1978 and 1998

Abstract: Objective: To investigate external-cause mortality among 21 609 Norwegian male military peacekeepers deployed to Lebanon during 1978Lebanon during -1998. Methods:The cohort was followed from first day of deployment through 2013, and mortality during deployment and post discharge was assessed using standardized mortality ratios (SMR) calculated from national rates in Norway. Poisson regression was used to see the effect of high-versus low-conflict exposure.Results: For the total cohort, external-cause mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“… Multination Haiti, Sierra Leone, Australia, Central Africa Interview, Medical report, Case study, Cohort study Dengue, Lassa fever, Dengue, Tungiasis. Other health problems Adams et al 1997 [ 92 ], Thoresen et al 2003 [ 93 ], Hu et al 2005 [ 64 ], Hébert et al 2007 [ 94 ], Li et al 2008 [ 95 ], Xie et al 2009 [ 71 ], Sun et al 2011 [ 96 ], Korzeniewski et al 2011 [ 97 ], Tian et al 2011 [ 98 ], Glad et al 2012 [ 99 ], Sun et al 2014 [ 100 ], Yang et al 2014 [ 101 ], Strand et al 2014 [ 102 ], Bolognesi et al 2016 [ 103 ], Zhou et al 2016 [ 104 ], Strand et al 2016 [ 105 ], Enkhtsetseg et al 2016 [ 106 ], Tang et al 2017 [ 107 ], He et al 2017 [ 80 ], Chen et al 2018 [ 108 ], Qi et al 2018 [ 82 ], Zhao et al 2018 [ 109 ],Wang et al 2018 [ 110 ], Bullman et al 2019 [ 111 ], Qi et al 2019 [ 112 ], Zuo et al 2020 [ 113 ], Liu et al 2021 [ 114 ] Korzeniewski, 2011 [ 115 ] Okulate, 2004 [ 116 ] Duarte, 2015 [ 117 ] Western Pacific Region: China Mali, Sudan, Lebanon, Liberia, South Sudan, The Democratic Republic of Congo Expert consultation, Retrospective study Respiratory diseases, Fracture, Intermittent diarrhea, Eczema, Insomnia, Mosquito bites, Trauma, Low back and leg pain, Oral ulcers, Injuries, Skin and soft tissue defects. Oral, skin, gastrointestinal, musculoskeletal, respiratory, urinary, ophthalmic, otolaryngologic and gynecological diseases, leukemia Region of the Americas: Canada, U.S., Brazil Bosnia, Kosovo, Haiti Case study, Cohort study, Medical report, Interview Musculoskeletal injuries, Mortality (leukemia, respiratory disease, respiratory cancer, and heart disease).…”
Section: Methodsmentioning
confidence: 99%
“… Multination Haiti, Sierra Leone, Australia, Central Africa Interview, Medical report, Case study, Cohort study Dengue, Lassa fever, Dengue, Tungiasis. Other health problems Adams et al 1997 [ 92 ], Thoresen et al 2003 [ 93 ], Hu et al 2005 [ 64 ], Hébert et al 2007 [ 94 ], Li et al 2008 [ 95 ], Xie et al 2009 [ 71 ], Sun et al 2011 [ 96 ], Korzeniewski et al 2011 [ 97 ], Tian et al 2011 [ 98 ], Glad et al 2012 [ 99 ], Sun et al 2014 [ 100 ], Yang et al 2014 [ 101 ], Strand et al 2014 [ 102 ], Bolognesi et al 2016 [ 103 ], Zhou et al 2016 [ 104 ], Strand et al 2016 [ 105 ], Enkhtsetseg et al 2016 [ 106 ], Tang et al 2017 [ 107 ], He et al 2017 [ 80 ], Chen et al 2018 [ 108 ], Qi et al 2018 [ 82 ], Zhao et al 2018 [ 109 ],Wang et al 2018 [ 110 ], Bullman et al 2019 [ 111 ], Qi et al 2019 [ 112 ], Zuo et al 2020 [ 113 ], Liu et al 2021 [ 114 ] Korzeniewski, 2011 [ 115 ] Okulate, 2004 [ 116 ] Duarte, 2015 [ 117 ] Western Pacific Region: China Mali, Sudan, Lebanon, Liberia, South Sudan, The Democratic Republic of Congo Expert consultation, Retrospective study Respiratory diseases, Fracture, Intermittent diarrhea, Eczema, Insomnia, Mosquito bites, Trauma, Low back and leg pain, Oral ulcers, Injuries, Skin and soft tissue defects. Oral, skin, gastrointestinal, musculoskeletal, respiratory, urinary, ophthalmic, otolaryngologic and gynecological diseases, leukemia Region of the Americas: Canada, U.S., Brazil Bosnia, Kosovo, Haiti Case study, Cohort study, Medical report, Interview Musculoskeletal injuries, Mortality (leukemia, respiratory disease, respiratory cancer, and heart disease).…”
Section: Methodsmentioning
confidence: 99%
“…Specific to peacekeeping, Laukkala et al [13] found that a history of peacekeeping service resulted in low general mortality. Strand et al [15] also found that peacekeeping service conferred a protective effect; however, an exception was made for neoplasms, whereby the protective effect dissipated within 5 years. In this cohort, a direct relationship was also noted between combat exposure and increased mortality from all external sources, motor vehicle accidents and suicides within 5 years of release from the military [15].…”
Section: Discussionmentioning
confidence: 97%
“…Korea [3], Vietnam [4], Falklands [5], Gulf War [6][7][8][9][10][11][12]), or specific military action (e.g. peacekeeping [13][14][15]). However, to the best of our knowledge, it is the first time that someone has studied a full military cohort (a census, of sorts) over a long period of time, and across multiple military involvements.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of disease-related mortality in this cohort, we found an HSE for all-cause mortality due to low mortality from diseases. However, no HSE was seen for external-cause mortality; instead a 29% excess was seen during the first 5 years of follow-up 22. The aim of the present study is to further investigate external-cause mortality, such as transport accidents and suicide, in the same cohort.…”
Section: Introductionmentioning
confidence: 85%
“…The study population, outcome registries and methodology were described in a previous study on this same cohort22 and are repeated only briefly. The study cohort was established by The Norwegian Armed Forces Human Resources and Conscription Centre and counts 21 609 Norwegian male military peacekeepers deployed to Lebanon during 1978–1998.…”
Section: Methodsmentioning
confidence: 99%